A QUALIDADE NA PRESTAÇÃO DE SERVIÇOS DE TRANSPORTES DA EXPRESSO SÃO MIGUEL AGÊNCIA DE TRÊS PASSOS-RS. - Hübner, Michel D.; Bianchini, Luciano; Pasqualini, Fernanda (Salão do Conhecimento, 2013)
Resumo